2021
DOI: 10.4236/ojs.2021.111005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Length of Stay (LOS) Data from the Medical Records of Tertiary Care Hospital in Saudi Arabia for Five Diagnosis Related Groups: Application of Cox Prediction Model

Abstract: Background: One of the main objectives of hospital managements is to control the length of stay (LOS). Successful control of LOS of inpatients will result in reduction in the cost of care, decrease in nosocomial infections, medication side effects, and better management of the limited number of available patients' beds. The length of stay (LOS) is an important indicator of the efficiency of hospital management by improving the quality of treatment, and increased hospital profit with more efficient bed manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…DRGs are primarily used to calculate reimbursement for each patient category. Studies in KSA reported a significant relationship between DRGs to the patient length of stay in the hospital, in addition to the patient's age ( Sara and Shoukri, 2021 ). In terms of financial impact, DRG is considered a reliable and patient services representative system preferred for reimbursement purposes ( Mehmood et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…DRGs are primarily used to calculate reimbursement for each patient category. Studies in KSA reported a significant relationship between DRGs to the patient length of stay in the hospital, in addition to the patient's age ( Sara and Shoukri, 2021 ). In terms of financial impact, DRG is considered a reliable and patient services representative system preferred for reimbursement purposes ( Mehmood et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%